Buen vivir as an alternative to sustainable development : lessons from Ecuador - Chassagne, Natasha (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores how communities understand and practice Buen Vivir, an alternative to the current model of sustainable development. Until recently, the concept of Buen Vivir has only been loosely articulated by practising communities and in progressive policy in countries like Ecuador. What it actually means has been unclear, and in the case of policy, contradictory. As such there has been a lack of understanding about exactly what Buen Vivir entails, its core principles and how to put it into practice. This book, based on extensive theoretical and field research of Buen Vivir as an alternative to sustainable development, fills that gap and offers a concrete way forward. Buen Vivir as an Alternative to Sustainable Development uses an ethnographic study in the Cotacachi County of Ecuador's highlands communities to explore how communities understand and practice Buen Vivir. Combining that with what we already know about the concept theoretically, this book then develops a framework for Buen Vivir with 17 principles for practice. Exploring Buen Vivir's evolution from its indigenous origins, academic interpretations and implications for development policy; to its role in endogenous, community-led change, this book will be of interest to policymakers, and development professionals. It will also be of great value to activists, students and scholars of sustainability and development seeking grassroots social and environmental change"--
Introduction -- The Brief History of Development and Sustainable Development -- Towards an Alternative to Development: The Growing Legitimacy of Post-Development -- Sustaining the 'Good Life': Buen Vivir as an Alternative to Sustainable Development -- Understandings of Buen Vivir in Ecuador's Cotacachi Canton -- Living Well and Buen Vivir: Practice vs. Policy? -- Challenging the Good Life -- Rethinking Sustainability: Making the Global Align with the Local -- Implementing Buen Vivir: The Practical Pathway to Transformation -- New Horizons for Socio-Eco Wellbeing: Concluding Remarks.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development -- Ecuador; Economic development -- Ecuador; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Development / General; NATURE / Ecology